Renaissance and resistance: modern French tapestry and collective craft - O'Mahony, C (Routledge, 2016)
Modern tapestry makers articulated aspirations and anxieties about creativity and craft amidst the economic and political instability of twentieth-century France. In 1946 Jean Cassou selected tapestry as the focus for the Musée national d’art moderne’s opening exhibition re-defining post-war France to itself and the world. Liberté, a 1943 tapestry from a cartoon drawn by Jean Lurçat inspired by a poem by Paul Éluard, woven clandestinely in the attic rooms of Suzanne Goubely’s Aubusson workshop, typifies this narrative. However, the contrast between Lurçat’s wartime writings on tapestry and a 1945 photo essay of Aubusson weavers at work by Robert Doisneau highlights the vigorous debates about where to locate this “renaissance” of tapestry, transformed from a courtly luxury into a collective and economically viable national craft industry. Tapestry was renewed as a modern medium through the collaboration of artist-cartoon makers and weaving workshops; the exhibition culture of galleries run by collectors such as Marie Cuttoli of Maison Myrbor, Jeanne Bucher and Denise Majorel of La Demeure; the administrators of the National Manufactures; and the work of art educators and craftworkers, A. Marius Martin and Pauline Peugniez. The embodied experience required to create and to understand tapestry, where individual and collective experience commingle, resonates with Simone De Beauvoir’s principle of “situated freedom”. In twenty-first century Aubusson, the new initiatives of the Cité de la Tapisserie and the Olympe de Gouges tapestries celebrate and promote these liberties.